Determination of kynurenic acid in rat cerebrospinal fluid by HPLC with fluorescence detection. (12th May 2015) - Bao, Ye; Luchetti, David; Schaeffer, Eric; Cutrone, Jingfang
Abstract: A sensitive HPLC method using fluorescence detection was developed to determine kynurenic acid (KYNA) level in rat cerebrospinal fluid (CSF). The method development was accomplished by screening different columns, optimizing zinc acetate concentration and determining the optimal HPLC flow rate. This method allowed direct injection of the CSF samples onto an Xselect C18 column and KYNA levels were measured fluorometrically by forming a fluorescent complex with zinc acetate that was delivered post‐column. The limit of quantitation was 0.2 nm with 30 μL injection, corresponding to 6 fmol (signal‐to‐noise ratio = 10). The improved sensitivity enabled the measurement of KYNA in naive and drug‐treated rat CSF. Copyright © 2015 John Wiley & Sons, Ltd.